Design of RC trigger circuit for dynamically activated ESD protections ensuring application requirements and ESD performances. (November 2022) - Merlo, L.; Di Biccari, L.; Cerati, L.; Andreini, A.
Abstract: The design of dynamically activated ESD protections requires an accurate analysis of the activation sensitivity versus the application requirements. In this work it is presented how the performances of HV Darlington ESD protection are impacted by its own RC trigger circuit, and a design methodology to properly define the RC value based on application constraints is discussed. The limitations in data extrapolating from 100 ns-TLP characterizations are shown, proposing an alternative approach that combines HBM characterization data and electrical simulations. Highlights: Dynamically activated ESD device design requires an analysis of the activation sensitivity vs. the application requirements The performances of HV Darlington ESD device are impacted by its trigger circuit The electrical behaviour in the Human Body Model tail can be confirmed as a correct indicator of the ESD device activation